An investigation into the feasibility of utilizing phytoliths to identify domesticated plants frequently used at Southern African archaeological sites - Hattingh, Tanya (My University, 2018)
A lack of macro-botanical remains often hampers investigations into the agricultural practices of precolonial farming communities in southern Africa. It has been suggested (see e.g. Pearsall 1982; Piperno 1984; Logan 2012) that phytoliths could be used to establish which plants were cultivated and used at archaeological sites, but few studies have explored the diagnostic value of the phytoliths produced by plants domesticated in Africa. This PhD will help to address this lacuna. Consequently, the aim of this research was to establish the diagnostic potential of African domesticates, including Eleusine coracana subsp. coracana, Pennisetum glaucum, Sorghum bicolor subsp. bicolor, Vigna subterranea and Vigna unguiculata subsp. unguiculata, as well as two naturalized plants, namely Zea mays and Arachis hypogaea. The phytoliths from different varieties of each crop were analysed to determine if there are significant differences between the phytoliths produced by them. During this study the phytoliths of mature and juvenile specimens of each domesticate were also evaluated in order to establish whether phytolith morphology changed with age. Lastly, a comparison between the morphology, length and width of the phytoliths from domesticated plants and selected wild taxa were compared to determine the diagnostic value of the phytoliths from each crop. My analysis showed that, based on the morphotypes and measurements that I considered, A. hypogaea, V. subterranea and V. unguiculata subsp. unguiculata phytoliths cannot be used to determine the presence of crops at archaeological sites. E. coracana subsp. coracana, P. glaucum and S. bicolor subsp. bicolor phytoliths have limited diagnostic potential, while Z. mays creates unique phytoliths that can be used as a proxy for crop usage at archaeological sites in southern Africa. Lastly, while there are no significant differences between the phytoliths from the juvenile and mature Fabaceae specimens that were analysed, there are some noteworthy variances between phytoliths from the juvenile and mature Poaceae samples.
A Thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2018